The Relationship Between Parental Knowledge About Stimulation and Child Development in Playgroup Classes in Bluru Kidul Village, Sidoarjo - Setyowati, Dewi; Ragil, Rinez Ananda; Andriyanti, Andriyanti (Rifa'Institute, 2026)
Introduction: Early childhood is a critical period for cognitive, language, motor, and social development. However, developmental problems remain a serious issue globally and in Indonesia. Objective: This study aims to analyze the relationship between parental knowledge about stimulation and child development in playgroup classes. Method: This analytical observational study used a cross-sectional design with 60 children and their parents from four early childhood education centers in Bluru Kidul Village, Sidoarjo. Parental knowledge was assessed using questionnaires, and child development was evaluated using the Pre-Screening Developmental Questionnaire (KPSP). Data were analyzed using Fisher's Exact Test. Results and Discussion: Most parents (51.7%) demonstrated good knowledge levels, and most children (73.3%) showed appropriate development. Fisher's Exact Test showed a significant association (p = 0.019) between parental knowledge and child development outcomes. Conclusion: There is a significant relationship between parental knowledge about stimulation and child development in playgroup-aged children. Strengthening parental knowledge and consistent stimulation practices are essential for optimal early childhood development